2022
DOI: 10.1038/s41598-022-25867-y
|View full text |Cite
|
Sign up to set email alerts
|

Developing a diagnosis model for dry eye disease in dogs using object detection

Abstract: The purpose of this study was to develop an object detection method for the diagnosis of dry eye disease (DED) in dogs. To this end, a methodology was designed to evaluate ocular surface video images using the YOLOv5 model, which is an object detection algorithm that has been widely used because of its simple network structure and fast detection speed. Because the cornea is a transparent organ, an illuminator plate with grid squares was used to provide grid lines, which were analyzed as the reflected straight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Previous studies used image classification to label entire images, while the current approach uses object detection to not only locate, but also label individual objects within an image. A study reported a YOLOv5 model for dry eye disease in dogs with a very high mAP of 0.995 40 . Another group built a model for dermatophytosis, mange and fleas 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies used image classification to label entire images, while the current approach uses object detection to not only locate, but also label individual objects within an image. A study reported a YOLOv5 model for dry eye disease in dogs with a very high mAP of 0.995 40 . Another group built a model for dermatophytosis, mange and fleas 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A study reported a YOLOv5 model for dry eye disease in dogs with a very high mAP of 0.995. 40 Another group built a model for dermatophytosis, mange and fleas. 38 Another model evaluated 12 dog skin diseases.…”
Section: Modelmentioning
confidence: 99%
“…The following method was used to evaluate NIBUT with the grid-line illuminator. Slit-lamp biomicroscope (GS LED Slit Lamp MW50D, Shigiya machinery works LTD., Japan) with an add-on custom-made grid-plate illuminator (a 42 cm × 33 cm plate with LED lights corresponding to a total of 19 squares × 15 squares of 2 cm 2 in size grid) was used to obtain a 20-s video of images from all patients ( Figures 1 , 2 ) ( 14 ). All videos were recorded prior to conducting any of the other examinations.…”
Section: Methodsmentioning
confidence: 99%
“…A modified version of the original NIBUT system developed by Mengher et al ( 13 ), which sheds a grid-shaped illumination on the corneal surface, has been used as the diagnostic method to evaluate the status of the ocular surface in this study. Previous studies on the use of grid-line illumination NIBUT system utilized an add-on illuminator plate over the commonly distributed ophthalmic slit-lamp biomicroscopes ( 14 ). The square grid lines of light reflected on the corneal surface represent the precorneal tear film (PTF), and the disturbance or disruption of these lines represents the break-up of the tear film ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation